Eliminating irreproducibility in SERS substrates. (28th October 2020) - Grys, David‐Benjamin; Chikkaraddy, Rohit; Kamp, Marlous; Scherman, Oren A.; Baumberg, Jeremy J.; de Nijs, Bart
Abstract: Irreproducibility in surface‐enhanced Raman spectroscopy (SERS) due to variability among substrates is a source of recurrent debate within the field. It is regarded as a major hurdle towards the widespread adoption of SERS as a sensing platform. Most of the literature focused on developing substrates for various applications considers reproducibility of lower importance. Here, we address and analyse the sources of this irreproducibility in order to show how these can be minimised. We apply our findings to a simple substrate demonstrating reproducible SERS measurements with relative standard deviations well below 1% between different batches and days. Identifying the sources of irreproducibility and understanding how to reduce these can aid in the transition of SERS from the lab to real‐world applications. Abstract : We analyse sources of irreproducibility in SERS substrates and demonstrate how these can be minimised to generate substrates with relative standard deviations (RSDs), well below 1% between batches and days. Identifying how RSDs can be reduced will aid in the transition of SERS from the lab to real‐world applications.